2023
DOI: 10.3390/pr11051302
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Reactor Temperature Control with Optimized PID Parameters Based on Improved Sparrow Algorithm

Abstract: To address the problems of strong coupling and large hysteresis in the temperature control of a continuously stirred tank reactor (CSTR) process, an improved sparrow search algorithm (ISSA) is proposed to optimize the PID parameters. The improvement aims to solve the problems of population diversity reduction and easy-to-fall-into local optimal solutions when the traditional sparrow algorithm is close to the global optimum. This differs from other improved algorithms by adding a new Gauss Cauchy mutation strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…SSA, as a swarm intelligence optimization algorithm, has proven its ability to search for optimization [35][36][37]. The position of the i-th sparrow is…”
Section: Mssamentioning
confidence: 99%
“…SSA, as a swarm intelligence optimization algorithm, has proven its ability to search for optimization [35][36][37]. The position of the i-th sparrow is…”
Section: Mssamentioning
confidence: 99%
“…The results indicated that the PSO-Fuzzy PID scheme significantly reduced disturbance adjustment time and eliminated overshoot, exhibiting superior control performance, although it might fall into local optima during computation, leading to inaccurate parameter adjustments. Mingsan Ouyang et al [15] introduced an improved sparrow search algorithm (ISSA) to optimize PID parameters in the temperature control process of a continuous stirred tank reactor (CSTR). Experimental results showed improved transient and steady-state performance of the reactor temperature control with good precision and robustness, although the convergence was poor after enhancing the capability to escape local minima.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism modeling method to obtain the temperature distribution is more explainable; however, the establishment of the model relies on many hypothetical conditions, many parameters require identification and the current solution process has low efficiency. The numerical simulation method is another method to intuitively display the temperature distribution [8][9][10][11]. A new methodology in [12] was proposed for converting the steady periodic operation of a metal-gas system into a steady-state problem for the reheating furnace, which significantly reduces the calculation time.…”
Section: Introductionmentioning
confidence: 99%